Perineal Trauma Impact on Postpartum Sexual Function: A Cross-Sectional Study Using Female Sexual Function Index - Karsa, Salsa Bila; Antonius, Puja Agung; Fitria, Henni; Insani, Aldina Ayunda; Fadila, Zurraya; Dimba, Modester (JIK-JURNAL ILMU KESEHATAN, 2025)
Background: Perineal trauma resulting from vaginal delivery can negatively impact postpartum sexual function; however, data from Southeast Asian populations are still scarce.Objective: We aimed to study the relationship between perineal trauma and sexual dysfunction measured by the Female Sexual Function Index (FSFI) among postpartum women in Indonesia.Methods: A cross-sectional study was carried out at Pauh Community Health Center, Padang City, between May and June 2025. We used purposive sampling to recruit forty-six women who had a vaginal delivery within the last six months. Sexual function was measured using the Indonesian FSFI version, a tool validated for the Indonesian population, with scores below 26.55 indicating dysfunction. Perineal trauma condition was ascertained from the medical record. The chi-square test assessed the association between perineal trauma and sexual dysfunction.Results: Sexual dysfunction prevalence was 54.3% (n=25). Of the women who had perineal trauma, 82.6% were sexually dysfunctional, compared to 26.1% in the group without trauma. The relationship was statistically significant (p=0.001) with a crude odds ratio of 13.81 (95% CI: 3.46-55.12). The pain and desire domains were affected the most.Conclusion: Perineal trauma is a significant risk factor for postpartum sexual dysfunction among Indonesian women. Besides that, health care workers should promote the sexual health of their clients by regularly integrating the screening of sexual health into routine postpartum care, applying evidence-based interventions to reduce perineal injury, and providing easy access to pelvic floor rehabilitation services as a way to improve maternal quality of life.